Ultrahigh Performance UV Photodetector by Inserting an Al2O3 Nanolayer in NiO/n‐Si - Vincent Teng (Advanced Electronic Materials, 2024)
Ultraviolet (UV) photodetectors have gained much attention due to their numerous important applications ranging from environmental monitoring to space communication. To date, most p-NiO/n-Si heterojunction photodetectors (HPDs) exhibit poor UV responsivity and slow response. This is mainly due to a small valence band offset (ΔEV) at the NiO/Si interface and a high density of dangling bonds at the silicon surface. Herein, an UV HPD consisting of NiO/Al2O3/n-Si is fabricated using magnetron sputtering technique. The HPD has a large rectification ratio of 2.4 × 105. It also exhibits excellent UV responsivity (R) of 15.8 A/W at −5 V and and detectivity (D*) of 1.14 × 1013 Jones at −4 V, respectively. The excellent performance of the HPD can be attributed to the defect passivation at the interfaces of the heterojunction and the efficient separation of photogenerated carriers by the Al2O3 nanolayer. The external quantum efficiency (EQE) of the HPD as high as 5.4 × 103%, hence implying a large optical gain due to carrier proliferation resulting from impact ionization. Furthermore, the ultrafast response speed with a rise time of 80 µs and a decay time of 184 µs are obtained.